Hanna Suomalainen 1874-1948 : Kuopion taidemuseossa 14.8.-20.9.1987 - Jaatinen, Aija; Moilanen, Irene; Tuomainen, Marketta; Halttunen, Inkeri; Hublin, Nils-G; Kuopion taidemuseo (Kuopion taidemuseon julkaisuja, ISSN 0782-2618, 1987)
Summary.
Keywords: Suomalainen, Hanna, : 1874-; näyttelyjulkaisut; maalaustaide